Engendering a maqasid worldview of gender roles in Malaysia: A content analysis of Che Husna Azhari’s Mariah (2003) and S.M. Zakir’s a sword-fighter’s love (2009) - Mohd Ezamir Azral, Mohd Azrul; Wan Ahmad Fauzi, Wan Husain (NUN Gemilang ENT., 2025)
The discourse on gender roles remains one of the most debated issues in modern Malaysia. While the country’s identity is rooted in religious and cultural heritage, a minority continues to promote gender debates through Western liberal philosophies, feminist critiques, and secular paradigms that emphasise individualism and relativism, often diverging from Malaysia’s socio-religious foundations. This study contributes to gender scholarship by proposing an alternative framework based on the maqasid al-shari‘ah and watanic jurisprudence, offering holistic, Quranic approaches to understanding gender. The research employs a qualitative case study design, analysing two Malaysian short stories written in English: Che Husna Azhari’s Mariah (2003) and S. M. Zakir’s A Sword-Fighter’s Love (2009). Methodologically, the analysis combines the maqasid al-shari‘ah with the watanic jurisprudential continuum, which contrasts Qur’anic integration of law and revelation with secular dichotomies that separate them. This dual approach enables a contextual reading that is both normatively grounded and culturally coherent. Findings indicate that, when examined through the maqasid–watanic framework, gender roles in the texts reflect balance, complementarity, and mutual responsibility, serving as divinely entrusted functions that uphold moral order, social cohesion, and spiritual wellbeing. This contrasts with secular-liberal interpretations, which often reduce gender to a matter of individual autonomy or power relations. The study argues that embedding maqasid and watanic jurisprudence in gender discourse allows for a more coherent and civilisationally authentic worldview, preserving Malaysia’s Islamic identity while critically engaging with global debates.